We Are Family: Specifying the Unique Contribution of Abuse and Neglect of Siblings on the Prevalence, Severity, and Chronicity of Maltreatment in the Household. Issue 15 (August 2018) - Spano, Richard
Prior research typically focuses on a single child ("index" victim) when measuring child abuse and neglect (CAN) using Child Protective Services (CPS) records. However, excluding siblings has the potential to underestimate estimates of the prevalence, severity, and chronicity of CAN in the household, which includes all children in the family. CPS maltreatment records were searched in 2005 for 366 "index" victims who were surveyed for 5 consecutive years (from 1998 to 2002) for the Mobile Youth Survey (MYS) as well as other siblings in the household. The estimate of prevalence of CAN in the household increased by 10% when sibling(s) in the household were included in the CPS search. In addition, prevalence of sexual abuse in the household increased by 38% when siblings were included in the broader search of CPS records. More importantly, including sibling victims of CAN uncovered incidents of maltreatment that occurred before the birth of the targeted MYS "index" victim. In short, the inclusion of abuse and neglect of siblings is a straightforward and intuitive way to improve estimates of abuse and neglect in the household. More importantly, the age of onset of CAN of sibling victims provides a wider window of opportunity to identify at-risk families for targeted interventions and may represent a critical stepping stone toward the primary prevention of CAN in the household.